GENDER EQUALITY IN THE LABOR MARKET OF UZBEKISTAN: PROBLEMS AND REFORMS (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This research examines the status of gender equality within the labor market of Uzbekistan, focusing on prevalent challenges and ongoing reform efforts. Through a comprehensive analysis of demographic data, educational trends, and employment patterns, the study investigates the disparities in workforce participation, wages, and occupational representation between men and women. The paper also delves into the underlying socio-cultural factors influencing gender dynamics within the labor market, including familial expectations and workplace practices. Moreover, it evaluates recent policy initiatives and institutional reforms aimed at promoting gender equality and fostering women's empowerment in the workforce. By synthesizing empirical evidence and policy analysis, this research provides insights into the complexities of gender inequality in Uzbekistan's labor market and offers recommendations for future interventions and policy directions.
Keywords: Gender equality, labor market, Uzbekistan, workforce participation, wage gap, occupational segregation, socio-cultural factors, policy reforms, women's empowerment.